Bioexploration and Phylogenetic Placement of Entomopathogenic Fungi of the Genus Beauveria in Soils of Lebanon Cedar Forests - Charbel Al Khoury (13167975) (2021)
The cedar forests of Lebanon have been threatened by the outbreak caused by climate change of a web-spinning sawfly, Cephalcia tannourinensis (Hymenoptera: Pamphiliidae), which negatively impacted the survival of one of the oldest tree species on earth. In this study, we investigated the occurrence of naturally soil-inhabiting entomopathogenic fungi for their role in containing the massive outbreak of this insect. We used a combination of fungal bioexploration methods, including insect bait and selective media. Morphological features and multilocus phylogeny—based on Sanger sequencing of the transcripts encoding the translation elongation factor 1-alpha (TEF-α), RNA polymerase II second largest subunit (RBP2), and the nuclear intergenic region (Bloc) were used for species identification. The occurrence rate of entomopathogenic fungi (EPF) varied with location, soil structure, forest structure, and isolation method. From 15 soil samples positive for fungal occurrence, a total of 249 isolates was obtained from all locations using different isolation methods. The phylogenetic analysis confirmed the existence of two novel indigenous species: Beauveria tannourinensis sp. nov. and Beauveria ehdenensis sp. nov. In conclusion, the present survey was successful (1) in optimizing the isolation methods for EPF, (2) investigating the natural occurrence of Beauveria spp. in outbreak areas of C. tannourinensis, and (3) in characterizing the presence of new Beauveria species in Lebanese cedar forest soil. Other Information Published in: Journal of Fungi License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/jof7110924